PENGARUH MODEL PEMBELAJARAN RADEC BERBANTUAN MEDIA PEMBELAJARAN BEBRBASIS CANVA TERHADAP LITERASI SAINS DAN HASIL BELAJAR IPAS SISWA KELAS V - Renaldi Suardi; Bancong, Hartono; Rukli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Study was motivated’ by students lack of scientific’ literacy and learning outcomes in IPAS subject. This study aimed to determine the influence of the RADEC learning model assisted by Canva-based learning media on scientific literacy and the learning outcomes of fifth-grade students in the IPAS subject. The research employed a quasi-experimental design with a pre-test post-test control group design. The study was conducted in two schools within the Anggeraja cluster, involving 60 fifth-grade students. Data were collected by tests, observation, and documentation. The result of the study by using paired sample T-tests showed a significance value of 0.00 < 0.05 for both variables, indicating that the RADEC learning model assisted by Canva- based learning media partially influenced the scientific literacy and IPAS learning outcomes of fifth-grade students. Furthermore, MANOVA tests revealed that all significance values obtained from each test sequence were 0.00 <0.05, indicating that the RADEC learning model assisted by Canva-based learning media and the conventional learning model had different influences on the scientific literacy and IPAS learning outcomes of fifth-grade students simultaneously.